PROBLEMATIKA PERS LOKAL DALAM MENGHADAPI KONTESTASI PEMILIHAN KEPALA DAERAH (PILKADA) DI PROVINSI SUMATERA BARAT - Dianto, Icol (Islamic Communication Journal, 2018)
AbstractLocal press problems in facing the contestation of the election of Regional Heads in West Sumatra Province can be grouped into two broad lines: first, the local press is dragged into a conflict of interest in the election of the Regional Head including 1) The Press supports one candidate pair, 2). Incitement of the success team, 3). The interests of media owners and stakeholders in media companies. Second, the intervention of the Regional Head towards local media includes 1). Change the Regional Head changes journalists, 2). Contract termination threats and 3). Media blockade. As for the solution to the problem, an alternative solution can be proposed that: 1). Re-guided Law Number 40 of 1999 concerning Press. 2). Balancing the press as a business industry with the press as a professional institution (social control). 3). The media owner should not use and manipulate his press company into the realm of practical politics. 5). In establishing cooperation with local governments, strive to stick to the principles and ethics of the journalistic profession. 6). Journalists must increase the capacity and quality of journalistic products, adhere to journalists code of ethics, and not bring the profession into the realm of practical politics. 7). Report regional heads or parties who attempt to intimidate the media and journalists in carrying out their profession, to the Public Information Commission (KIP), police and Ombudsman at certain levels of government.Keywords: Local Press, Problems, Pemilukada Contestation.Â AbstrakProblematika pers lokal dalam menghadapi kontestasi pemilihan Kepala Daerah di Provinsi Sumatera Barat dapat dikelompokkan pada dua garis besar: yaitu pertama, pers lokal terseret dalam konflik kepentingan pemilihan Kepala Daerah meliputi 1) Pers mendukung salah satu pasangan calon, 2). hasutan tim sukses, 3). kepentingan pemilik media dan pemangku kewenangan pada perusahaan media. Kedua, intervensi Kepala daerah terhadap media lokal meliputi 1). berganti Kepala Daerah berganti wartawan, 2). ancaman putus kontrak dan 3). blokade media. Adapun solusi untuk permasalahan tersebut, dapat diajukan alternative penyelesaiannya bahwa: 1). Mempedomani kembali Undang-Undang Nomor 40 tahun 1999 tentang Pers. 2). Menyeimbangkan antara pers sebagai industry bisnis dengan pers sebagai lembaga professional (control social). 3). Pemilik media jangan memanfaatkan dan memperalat perusahaan pers miliknya ke ranah politik praktis. 5). Dalam menjalin kerja sama dengan pemerintah daerah, upayakan tetap berpegang pada prinsip dan etika profesi jurnalistik. 6). Wartawan mesti meningkatkan kapasitas dan kualitas produk jurnalistiknya, menaati kode etik wartawan, dan tidak membawa profesi ke ranah politik praktis. 7). Melaporkan kepala daerah atau pihak-pihak yang berupaya mengintimidasi media dan wartawan dalam menjalankan profesinya, ke Komisi Informasi Publik (KIP), polisi dan ombusman pada level pemerintahan tertentu.Kata Kunci: Pers Lokal, Problematika, Kontestasi Pemilukada.